Effects of fermented and supplemented chicken manure on the nutrient management aspects of an apple orchard - Tóth, Florence Alexandra; Tamás, János; Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2023)
AIt is a huge challenge for farmers worldwide to successfully increase the organic matter content of their soils and improve their water balance at the same time. Therefore, the main aim of the study is to develop and test organic-based nutrient composite materials that can be successfully used by farmers to increase soil organic matter content, improve water management parameters and implement water-efficient technologies. The study was performed in the orchard of the Institute of Horticultural Science of the University of Debrecen in Hungary (Debrecen-Pallag). The experiment was set up in a ten-year-old apple (Malus domestica ‘Pinova’) orchard. In the trial, fermented poultry manure and superabsorbent polymers (SAP) were used at different doses to study their effects on soil properties and fruit quality. Applied composite materials increased the nitrate and organic nitrogen content of the soil. Treatments did not affect the sugar content of the fruits but significantly and positively affected the individual fruit weight and the titratable acidity of the fruits.